Effects of blue light treatment on agility in badminton players - Kim, C.; Choi, J.; Ji, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Blue light has been shown to be comparatively effective to regulation of the human circadian clock contrast to bright light (~10,000lux). Therefore, it is possible for blue light to be effective to physical function of badminton players who work out indoor. The purpose of this study is to exam the effects of blue light treatment on physical performance, especially agility, of highly skilled badminton players. Thirtyseven international badminton players were tested on three separate occasions with the crossover counterbalanced design. In session 1, they tested agility test without any treatment as adaptation of the agility test. Session 2 served as placebo treatment by low white light (~200lux) for 30min and session 3 served as blue light treatment by lighting blue light (HF3431) to players for 30 minutes before agility test. As results, placebo treatment (~200lux low white light) improved agility time significantly [46.8(3.3) vs. 43.0(3.3), p<.05]. However, Blue light treatment showed more improvement significantly than low light treatment (placebo treatment) [43.0(3.3) vs. 42.1(3.1), p<0.5]. These findings indicated that blue light treatment can improve physical performance for elite athletic players who have risks for lack of sunlight.